UPAYA PENINGKATAN HASIL BELAJAR SISWA DENGAN MODEL PEMBELAJARAN CASE STUDY PADA MATA PELAJARAN PEMELIHARAAN MESIN SEPEDA MOTOR DI SMK TAMAN KARYA MADYA PERTAMBANGAN KEBUMEN - Fikri Sahrul Hidayat; Dwi Jatmoko; Aci Primartadi; Risky Ahdiat Setiadi; Hafid Nur Rahman (STKIP Subang, 2026)
This study aims to improve student learning outcomes through the Case Study learning model on the subject of Motorcycle Engine Maintenance (PMSM) for class XI TSM 1 students at SMK Taman Karya Madya Pertambangan Kebumen. This research uses a Classroom Action Research (CAR) method conducted in two cycles. The research subjects were 35 students of class XI TSM 1. Data collection techniques used observation, written tests, and documentation. Data analysis used quantitative analysis based on test results in each cycle. The results showed that the application of the Case Study learning model successfully improved student learning outcomes. The average score increased from 68.57 in the pre-cycle stage to 74.71 in Cycle 1, and further increased to 81.57 in Cycle 2. Meanwhile, the percentage of students achieving the Minimum Competency Criteria (KKM ≥ 80) increased from 20% in the pre-cycle to 40% in Cycle 1, and rose significantly to 82% in Cycle 2, exceeding the success indicator of ≥75%. These findings confirm that the Case Study learning model is effective in improving student learning outcomes on the topic of automatic transmission systems (CVT).